The utility of resting pulse rate in deﬁning high blood pressure among adolescents in Mbarara municipality, Uganda - Katamba, Godfrey; Agaba, David Collins; Namayanja, Rosemary; Namaganda, Agnes; Musasizi, Abdul; Kinene, Mivule Abdul; Migisha, Richard (ournal of Human Hypertension, 2021)
High resting pulse rate (RPR) is associated with adverse cardiovascular events and could be used as a marker of cardiovascular health. We determined the correlation between RPR and blood pressure (BP); and its accuracy in deﬁning high blood pressure among adolescents attending secondary schools in Mbarara municipality, south-western Uganda. We conducted a cross-sectional study among secondary school adolescents aged 12–19 years in Mbarara municipality, Uganda. We captured demographic characteristics using a structured questionnaire; and measured anthropometric indices and BP. We performed a linear regression analysis to determine the relationship between RPR and blood pressure and plotted receiver operating characteristics curves (ROC) to assess the accuracy of RPR in deﬁning high BP. We enrolled 616 adolescents with a mean age of 15.6±2.0 years and 65.6% (404/616) were female. The RPR was signiﬁcantly correlated with diastolic blood pressure (DBP) in both boys (Beta=0.22 [95% CI: 0.10; 0.36]), p<0.001 and girls (Beta=0.51 [95% CI: 0.43; 0.60]), p< 0.001. RPR was signiﬁcantly correlated with systolic blood pressure (SBP) only in the girls (Beta=0.23 [95% CI: 0.15; 0.30]), p<0.001. The optimal threshold for RPR in deﬁning prehypertension was RPR≥76bpm with an area under the curve (AUC) of 0.653 [95% CI: 0.583–0.722], the sensitivity of 0.737 and speciﬁcity of 0.577. In deﬁning hypertension, the optimal threshold was RPR≥79bpm at a sensitivity of 0.737 and speciﬁcity of 0.719, with an AUC of 0.728 [95% CI: 0.624–0.831]. Resting pulse rate was positively correlated with BP and was more accurate in deﬁning hypertension compared to prehypertension in the study.
Keywords: High resting pulse rate (RPR); Cardiovascular events; High blood pressure; Adolescents; Uganda; Hypertension